SPECTRUM OF SYSTEMIC SCLEROSIS IN PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL IN PAKISTAN: Spectrum of Systemic Sclerosis - Khaliq, Taqdees; Aziz, Wajahat; Farooqi, Abid (Pakistan Armed Forces Medical Journal, 2014)
Objective: To examine the clinical and laboratory features in the patients of systemic sclerosis coming to a tertiary care hospital in Islamabad, Pakistan. Study Design: Observational cross-sectional study. Place and Duration of Study: Study was conducted at the department of Rheumatology in Pakistan Institute of Medical Science between May 2012 and April 2013. Subjects and Methods: Both male (n=5) and female (n=40) patients of Systemic sclerosis (SSc) who presented in the Rheumatology outpatient department (OPD) were recruited in the study with informed consent. All the patients enrolled in the study fulfilled the American College of Rheumatology (ACR) criteria for diagnosis of SSc. Results: The mean age of the patients was 35.77 ± 13.10 years. Out of 45 patients, 28 (62%) had limited cutaneous systemic sclerosis (LcSS) and 17 (38%) had diffuse cutaneous systemic sclerosis (DcSS). Mean duration of disease was found to be 4.72 ± 4.78 years. Anti-nuclear antibody (ANA) positivity was seen in 80% of the patients. The most common clinical feature of the disease was Raynaud’s phenomenon (100%) followed by microstomia (98%), sclerodactyly (91%), digital pitting (89%), digital ulcers (82%) and arthralgias (73%). Among the constitutional symptoms fatigue was the most common one reported by 93% of the patients. Conclusion: Clinical features of systemic sclerosis examined in this cohort of patients were found to be consistent with the findings from other Asian countries.